Do public banks have a competitive advantage? - Astrid Matthey (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Private banks often blame state guarantees to distort competition by giving public banks the advantage of lower funding costs. In this paper I show that if borrowers perceive the public bank as supporting economic development, private banks may be able to separate firms by self selection, enter the market, and obtain profits in equilibrium despite their cost disadvantage. The public banks competitive advantage may be offset, independently of what its true objective function is. Even perfect competition between private banks does not lead to zero profits.
Keywords: G21; 330; public banks; state guarantee; self-selection; Öffentliche Bank; Staatshaftung; Wettbewerb; Bank; Kreditgeschäft; Agency Theory; Theorie